EVALUATION OF CYTOTOXIC PROPERTIES OF SOME DENTAL MATERIALS Zbigniew Raszewski* (Applied Biological Research, 2023)
In this study we compared the cytotoxic properties of several dental  materials on cell cultures. Six products chosen for the study were alginate  impression material, zinc phosphate cement, tissue conditioner for  temporary denture soft relining, acrylic temporary crown and bridge  material, heat curing acrylic resin and acrylic teeth. The samples were tested  forcytotoxic properties by MTT test on Vero CCL-81 (ATCC) cell line. The  most cytotoxic potential was observed for zincphosphate cement sample  (cell survival, 5%) and highest biocompatibility for thermally polymerized  acrylic resin (>70%). On exposure of dental materials to cytotoxic  properties it did not completely cross out the product, being developed as a  Medical Device. However, it requires further appropriate testing.
Keywords: Acrylic resin; alginate impression material; cytotoxicity; zinc phosphate cement